"What Gets Measured Gets Done": Metric Fixation and China's Experiment in Quantified Judging. Issue 2 (5th June 2021) - Ng, Kwai Hang; Chan, Peter C. H.
Abstract: This article analyzes the ambitious Case Quality Assessment System (CQAS) that the Supreme People's Court of China (SPC) promoted during the first half of the 2010s. It offers a case-study of Court J, a grassroots court located in an affluent urban metropolis of China that struggled to come out ahead in the CQAS competition. The article discusses how the SPC quantified judging and the problems created by the metricization process. The CQAS project is analyzed as a case of metric fixation. By identifying the problems that doomed the CQAS, the article points out the challenges facing the authoritarian regime in subjecting good judging to quantitative output standards. The CQAS is a metric that judges judging. It reveals how judging is viewed by the party-state. The article concludes by discussing the legacy of the CQAS. Though it nominally ended in 2014, key indicators that it introduced for supervising judges are still used by the Chinese courts today. The CQAS presaged the growing centralization that the Chinese judicial system is undergoing today. Though the SPC has terminated the tournament-style competition that defined the CQAS, the metric remains the template used to evaluate judging.